Analysis of the availability and water requirements of dryland farming and the water needs of residents in Hiri Island, Ternate City, North Maluku - Hadun, Ramli; Umasugi, Buhari; Sudjud, Suratman; Teapon, Amiruddin (Journal of Degraded and Mining Lands Management, 2024)
Dryland farming is one of the main agricultural models farmers use on the islands of North Maluku, so it is very dependent on the availability of rainwater. The water for crops is available in the rainy season, and drought is experienced in the dry season, one of which occurs on Hiri Island. This study aimed to analyze the availability and water needs of plants based on land characteristics and use to provide information for the development of dryland farming on Hiri Island. The method for calculating water availability used the land water balance approach using rainfall data for the last ten years, while the analysis of plant water needs was based on the soil moisture content and plant coefficient approach. The results of the analysis of water availability based on the land water balance of 2,236.4 mm with an average monthly rainfall of 186.4 mm and according to the type of land use on Hiri Island show that the highest available water in agroforestry was 40.92% in the secondary forest was 39.04%, in coconut, plantations was 35.72%, in fields was 35.18%, and undergrowth was 34.67%. Plant cultivation businesses must meet the water needs of plants to increase production. The people on Hiri Island need 29,340 L of water to fulfill their daily needs.